Men under stress - "Grinker, Roy R." (New York, 1963)
Out of World War II comes this classic analysis of Army Air Force combat fliers under the manifold threats and strains of battle. The authors worked with thousands of mentally-wounded soldiers overseas and in state side rehabilitation centers. They have selected sixty five case histories to reveal reactions during and after combat, as well as the effects of psychotherapy, narcosynthesis and other treatments. A final section on civilian applications underlines the immediacy and fascination of this remarkable book.
Keywords: Psychology